C07 The Influence Of Obesity And Reduced Food Intake On The Behavioural Characterisation Of The Bachd Rat Model Of Huntington Disease. (17th September 2014) - Jansson, E; Clemens, LE; Riess, O; Phuc Nguyen, H
Abstract : Background: Transgenic animals that carry the full-length HD-causing gene are generally heavier than their wild type (WT) littermates, which can be problematic during behavioural characterisation. Aims: To assess food intake and body composition of the BACHD rat model of Huntington disease, as well as investigating how the apparent phenotypes could affect performance in operant conditioning tests. Methods: Food consumption was measured longitudinally in a large group of animals housed in genotype-matched pairs. Animals under the same housing conditions were subjected to thorough dissections for body composition analysis. Further, performance in a progressive ratio test was investigated using two different food restriction protocols. In this test, rats are prompted to lever-push for a small food reward. The number of lever pushes required for reward delivery gradually increases and rats eventually lose interest, giving a measurement of motivation. Results: BACHD rats consumed less food compared to WT rats during most of the food consumption study, but still developed obesity. In the progressive ratio test, BACHD rats were less motivated than WT rats when both were deprived to 85% of their respective free-feeding body weights. Such a phenotype is of interest, as it could be an indicator of apathy, a common symptom among HD patients. However, the rats were equally motivated when the deprivation level of the WT rats has been adjusted so that their apparent food interest was equal to that of the BACHD rats. Conclusions: The reduced motivation initially seen among BACHD rats was most likely caused by a difference in hunger, rather than a psychological deficit. This was in turn probably connected to their obesity and lower food intake. This should be taken into consideration when working with behavioural characterisation of BACHD rats and other disease models with similar body composition and food intake phenotypes.